A Geographical Analysis of the Population Growth of Chamchamal District (2000-2018) - حمەیوسف, عطا حمەلاو; علی, هاودین كامل (Sulaimani Journal for Humanities, 2020)
Research on the nature of population growth in any place is considered an important subject, because planers use these types of researches as a main tool in the process of planning, identifying both population needs, and the magnitude of future population growth. Because of the importance of these types of researches, researchers have carried out researches on the nature of population growth in chamchamal district between the years(2000_2018).the research identifies the most important factors that affect the nature of population growth in the district and it analyzes those factors that affected the nature of population growth in the district،The result of the research shows that the totall birth rate in the district was (32.4) person in a thousand and the death rate was ( 0.3) person in a thousand. Also, the total natural growth that was (32.1) person in a thousand was obtained by getting the differences of the two birth and death rates. This shows that the total increase in the nature of the population in the district of the research had a good impact on population growth. The Research suggests solving any problems in the data by opening both death and birth documents in all the administrative unites in the researched areas, transferring the available death and birth data into electronic forms, and opening forensic medicine departments in the research areas.